A psicologia e as intervenções assistidas por animais como relação de cuidado: um estudo fenomenológico da literatura - BASTOS, Felipe Fook (2021)
The investigation intends to know how Animal Assisted Interventions as an emerging practice of Psychology through the Phenomenology of Edmund Husserl (1859-1938). Thus, the following interventional practices are accepted as Animal Assisted Interventions: Education, Therapy and Animal Assisted Activity. It is understood as an interdisciplinary intervention characterized by the presence of a non-human animal, and aimed at benefits for humans. It expects a congruence of the epistemological, theoretical and methodological framework, a phenomenology that allows us to comprehend the meaning of knowledge published by Psychology professionals about this theme. It will investigate the technical-scientific productions on Animal Assisted Interventions, produced by Psychology professionals through a phenomenological analysis. Therefore, the guiding question is: what are the meanings revealed by a phenomenological analysis of technical-scientific productions about Animal Assisted Interventions produced by professionals of Psychology? Reaching, then, the evidence of ethical relationships and care in these productions. Furthermore, the possibility of Animal Assisted Interventions in the process of psychological assessment and intervention is discussed; the intentions of these professionals are problematized, evident in the productions raised, when carrying out evaluations and interventions mediated by animals; and systematize the ways in which the phenomena of care and ethics are evidenced in the literature on Animal Assisted Interventions.